Continuous meteorological observations at station Ny-Ålesund (2025-05) - Maturilli, Marion (Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Potsdam, 2025)
The meteorological observatory Neumayer continuously acquires meteorological parameters. Measurements are taken on or near the meteorological 10m-mast, located some 300m south-east of the main station building. Co-located there are BSRN (Baseline Surface Radiation Network) measurements taken. The measurement interval of the raw data is approximately 6s. Data is quality controlled: All measurements are checked daily on site and again prior to publication according to BSRN standards. Knowingly affected or erroneous data is removed.